2008
DOI: 10.1063/1.2998612
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Al–Zn–Sn–O thin film transistors prepared at low temperature

Abstract: We have fabricated transparent bottom gate thin film transistors (TFTs) using Al-doped zinc tin oxide (AZTO) as active layers. The AZTO active layer was deposited by rf magnetron sputtering at room temperature. The AZTO TFT showed good TFT performance without postannealing. The field effect mobility and the subthreshold swing were improved by postannealing below 180 °C. The AZTO TFT exhibited a field effect mobility (μFET) of 10.1 cm2/V s, a turn-on voltage (Von) of 0.4 V, a subthreshold swing (S/S) of 0.6 V/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 10 publications
0
59
0
Order By: Relevance
“…Therefore, the role of the carrier-suppressor appears to influence carrier concentration, Hall mobility, and device stability due to its high oxygen-bonding ability. Cost-efficient ZnSnO-matrix-based oxide semiconductors have been under investigation with the addition of a variety of carrier-suppressors due to the high-cost and scarcity of indium and gallium [47,51]. Cho et al [51] reported an amorphous AlZnSnO TFT, that exhibited μ fe of 10.1 cm 2 /V · s, S of 0.6 V/ decade, and drain current on/off ratio of 10 9 after annealing at 180°C.…”
Section: Multicomponent Oxide Semiconductorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the role of the carrier-suppressor appears to influence carrier concentration, Hall mobility, and device stability due to its high oxygen-bonding ability. Cost-efficient ZnSnO-matrix-based oxide semiconductors have been under investigation with the addition of a variety of carrier-suppressors due to the high-cost and scarcity of indium and gallium [47,51]. Cho et al [51] reported an amorphous AlZnSnO TFT, that exhibited μ fe of 10.1 cm 2 /V · s, S of 0.6 V/ decade, and drain current on/off ratio of 10 9 after annealing at 180°C.…”
Section: Multicomponent Oxide Semiconductorsmentioning
confidence: 99%
“…Cost-efficient ZnSnO-matrix-based oxide semiconductors have been under investigation with the addition of a variety of carrier-suppressors due to the high-cost and scarcity of indium and gallium [47,51]. Cho et al [51] reported an amorphous AlZnSnO TFT, that exhibited μ fe of 10.1 cm 2 /V · s, S of 0.6 V/ decade, and drain current on/off ratio of 10 9 after annealing at 180°C. Later, Fortunato et al [52] developed an amorphous GaSnZnO channel layer, produced by rf magnetron cosputtering using gallium zinc oxide (GZO) and tin (Sn) targets.…”
Section: Multicomponent Oxide Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous research on oxide-semiconductor thin-film-transistors (OS-TFTs) has resulted in initial characteristics that are superior to those of a-Si; however, their long-term stability is still a problem to be overcome [9,10]. Recently, oxide semiconductors without indium have attracted attention because indium is becoming more expensive [11,12]. AMOLED prototypes using OS-TFTs have been developed by a few manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…Oxide TFTs with an active layer composed of Al 2 O 3 -ZnO-SnO 2 (AZTO) and sputtered at room temperature have been reported by these researchers. [12] The AZTO material is very stable chemically, and the sputtering method has the advantages of low cost and large-area uniformity among the various existing deposition methods. Therefore, the AZTO TFT is a prominent device for driving the large-size AMOLED panel.…”
Section: Introductionmentioning
confidence: 99%